Manajemen Sumber Daya Insani dalam Pengelolaan Heritage Pesantren - Nur Afifah, Isnaini; Noor Hasan, Dony Burhan (Journal Pemberdayaan Masyarakat Indonesia, 2022)
The purpose of this study describes the management of pesantren cultural heritage by pesantren human resources which includes planning, recruitment, and evaluation of human resource development in pesantren. This research uses a qualitative descriptive approach. The location of this study is in Pesantren Annuqayah Guluk-Guluk Sumenep. Data collection techniques using interview methods, documentation and observation. Informants in this study included pesantren caretakers and regional and central pesantren caretakers. The form of data in this study is primary data and secondary data obtained from informants and supporting documents. Analysis of data through descriptive analysis. The results showed that the cultural heritage of pesantren Annuqayah in the form of (1) manuscripts of books written by the caretakers of pesantren, Jami' Mosque, and grave the founder of pesantren Annuqayah; (2) the management of human resources in the management of pesantren heritage includes analysis of human resource development, recruitment process, education and training programs, formation of pesantren culture, as well as evaluations that are emphasized on changes in attitudes and behaviors in carrying out duties and responsibilities.